La documentación lingüística en la investigación de lenguas en la Amazonía peruana - Valqui, Jairo (2014)
This paper discusses an experience in language documentation in the Peruvian Amazon in order to reflect on some methodological dimensions that may extend to the linguistic research. The aim of this paper is to show that methodologies and the use of computer programs in language documentation can improve the analysis in any field of linguistics.